2020
DOI: 10.1111/aji.13248
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent structural and immunological changes in the placenta and fetal brain in response to systemic inflammation during pregnancy

Abstract: Problem Systemic maternal inflammation is associated with adverse neonatal sequelae. We tested the hypothesis that IL‐1β is a key inflammatory regulator of adverse pregnancy outcomes. Method of study Pregnant mice were treated with intraperitoneal injections of IL‐1β (0, 0.1, 0.5, or 1 μg) from embryonic day (E)14 to E17. Placenta and fetal brains were harvested and analyzed for morphologic changes and IL‐1β signaling markers. Results As compared with non‐treated dams, maternal injections with IL‐1β resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 89 publications
1
28
0
Order By: Relevance
“…We assayed cytokine mRNA expression during SARS-CoV-2 infection as a biomarker for inflammation. Because IL-1β activation during pregnancy can cause adverse fetal outcomes 2,14,15 , we measured IL1β mRNA expression in maternal blood, cord blood, and the maternal and fetal sides of placentas, which did not differ between SARS-CoV-2 positive and negative pregnant women ( Figure 1A-D ). To test whether IL1β expression differed as a function of maternal symptoms, samples were further categorized based on whether pregnant women were asymptomatic, symptomatic, or SARS-CoV-2 negative.…”
Section: Resultsmentioning
confidence: 99%
“…We assayed cytokine mRNA expression during SARS-CoV-2 infection as a biomarker for inflammation. Because IL-1β activation during pregnancy can cause adverse fetal outcomes 2,14,15 , we measured IL1β mRNA expression in maternal blood, cord blood, and the maternal and fetal sides of placentas, which did not differ between SARS-CoV-2 positive and negative pregnant women ( Figure 1A-D ). To test whether IL1β expression differed as a function of maternal symptoms, samples were further categorized based on whether pregnant women were asymptomatic, symptomatic, or SARS-CoV-2 negative.…”
Section: Resultsmentioning
confidence: 99%
“…2,10,11 We assayed cytokine mRNA expression during SARS-CoV-2 infection as a biomarker for inflammation. Because IL-1b activation during pregnancy can cause adverse fetal outcomes, 2,19,20 we measured IL-1b mRNA expression in maternal blood (total, 27; positive, 18; negative, 9), cord blood (total, 29; positive, 20; negative, 9), and the maternal (total, 11; positive, 8; negative, 1) and fetal (total, 26; positive, 19; negative, 7) sides of the placentas, which did not differ between pregnant women with and without SARS-CoV-2 infection (Figure 1, AeD). To assess whether the expression of IL-1b differed depending on the number of days between a…”
Section: Cytokine Expression After Severe Acute Respiratory Syndrome Coronavirus 2 Infection During Pregnancymentioning
confidence: 99%
“…20 Taken together, the cytokine storm (pro-inflammatory cytokines) induced by SARS-CoV-2 might place pregnant women at greater risk by causing an increased pro-inflammatory state with the potential to impact fetal brain development; thus, increasing the risk for autism, mental health disorders or schizophrenia. 26,[32][33][34] Currently, there are no studies reported on decidual immune cell interactions with SARS-CoV-2, but there are studies on the effect of SARS-CoV-2 on peripheral blood leukocytes. One key difference noted in peripheral blood leukocytes from those suffering severe COVID-19 symptoms, versus those with mild symptoms, was a decrease in IFN-γ and TNF-α in CD4+ T cells from the severe symptoms group.…”
Section: Immunology Of Covid-19 In Pregnancymentioning
confidence: 99%
“…A recent systematic review identified increased level of C‐reactive protein (CRP) in a majority of COVID‐19 positive pregnant women 20 . Taken together, the cytokine storm (pro‐inflammatory cytokines) induced by SARS‐CoV‐2 might place pregnant women at greater risk by causing an increased pro‐inflammatory state with the potential to impact fetal brain development; thus, increasing the risk for autism, mental health disorders or schizophrenia 26,32‐34 …”
Section: Introductionmentioning
confidence: 99%